Current use of baseline medical treatment in chronic rhinosinusitis: Data from the National Chronic Rhinosinusitis Epidemiology Study (CRES). (11th December 2017) - Philpott, C.; Erskine, S.; Smith, R.; Hopkins, C.; Kara, N.; Farboud, A.; Salam, M.; Robertson, A.; Almeyda, R.; Kumar, B.N.; Anari, S.; Ray, J.; et al.
Abstract : Objectives: According to clinical and comissioning guidelines for chronic rhinosinusitis (CRS), patients being referred to secondary care should have failed primary medical treatment with nasal douching (ND) and intranasal corticosteroids (INCS). The study objectives were to identify the rate of specific medical therapy in CRS patients and establish any differences in medication use, for both CRS and associated medical conditions, between CRS phenotypes. Design and setting: Case–control study in a secondary care setting. Methods: Participant‐reported study‐specific questionnaire capturing free text data on current medication use at the time of study entry. Qualitative interviews with 21 participants also explored their experience of CRS and its management. Particpants: Patients both without (CRSsNPs) and with polyps (CRSwNPs). Main outcome measures: Reported use of CRS‐related and non‐related medications. Results: Within a total of 1243 CRS participants, current INCS usage was low (18% in CRSwNPs, 12% in CRSsNPs); ND was being performed by only 1% of all participants. Bronchodilators and inhaled corticosteroids use was significantly higher in CRSwNPs participants ( P < .0001). Antidepressant use was significantly higher in CRSsNPs (14% vs 7%, P < .0002). There were no significant regional variations in rates of INCS use, nor any significant influence of social deprivation. Conclusions: The current use of baseline medical therapy in CRS appears to be very low, representing a combination of poor patient compliance, possible ineffectiveness of treatment and a lack of familiarity with current guidelines amongst general practitioners and some ENT specialists. Work is needed to disseminate guidelines to all practitioners involved and reduce unnecessary burden on existing healthcare resources for this common condition by ensuring timely referral and definitive management.